Strategies to Reduce Post-Hemorrhoidectomy Pain: A Systematic Review - Varut Lohsiriwat; Romyen Jitmungngan (Medicina, 2022)
Background and Objectives: Excisional hemorrhoidectomy is considered as a mainstay operation for high-grade hemorrhoids and complicated hemorrhoids. However, postoperative pain remains a challenging problem after hemorrhoidectomy. This systematic review aims to identify pharmacological and non-pharmacological interventions for reducing post-hemorrhoidectomy pain. Materials and Methods: The databases of Ovid MEDLINE, PubMed and EMBASE were systematically searched for randomized controlled trails (published in English language with full-text from 1981 to 30 September 2021) to include comparative studies examining post-hemorrhoidectomy pain as their primary outcomes between an intervention and another intervention (or a sham or placebo). Results: Some 157 studies were included in this review with additional information from 15 meta-analyses. Fundamentally, strategies to reduce post-hemorrhoidectomy pain were categorized into four groups: anesthetic methods, surgical techniques, intraoperative adjuncts, and postoperative interventions. In brief, local anesthesia-alone or combined with intravenous sedation was the most effective anesthetic method for excisional hemorrhoidectomy. Regarding surgical techniques, closed (Ferguson) hemorrhoidectomy performed with a vascular sealing device or an ultrasonic scalpel was recommended. Lateral internal anal sphincterotomy may be performed as a surgical adjunct to reduce post-hemorrhoidectomy pain, although it increased risks of anal incontinence. Chemical sphincterotomy (botulinum toxin, topical calcium channel blockers, and topical glyceryl trinitrate) was also efficacious in reducing postoperative pain. So were other topical agents such as anesthetic cream, 10% metronidazole ointment, and 10% sucralfate ointment. Postoperative administration of oral metronidazole, flavonoids, and laxatives was associated with a significant reduction in post-hemorrhoidectomy pain. Conclusions: This systematic review comprehensively covers evidence-based strategies to reduce pain after excisional hemorrhoidectomy. Areas for future research on this topic are also addressed at the end of this article.